2009
DOI: 10.5897/ajb09.1080
|View full text |Cite
|
Sign up to set email alerts
|

Morphological abnormality among regenerated shoots of banana and plantain (Musa spp.) after in vitro multiplication with TDZ and BAP from excised shoot-tips

Abstract: Five cultivars ofand 'Rastali' and 5 µM for 'Berangan Intan' and 'Berangan' increased the number of shoots per explant, however TDZ at 5 µM resulted in high number of abnormal shoots. In conclusion BAP at 22.2 µM and TDZ at 2 µM were assumed to be the most suitable for commercial micropropagation system with low frequency of abnormal shoot production for both banana and plantain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Thus, this phenomenon could result also from micropropagation process. Multiplication of plants by this technique, can induce phenotypic aberrations in ex vitro cultivations that were not observed during in vitro culturing (Shirani et al 2009;Iliev and Kitin 2011;Chiruvella et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this phenomenon could result also from micropropagation process. Multiplication of plants by this technique, can induce phenotypic aberrations in ex vitro cultivations that were not observed during in vitro culturing (Shirani et al 2009;Iliev and Kitin 2011;Chiruvella et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The application of BA is considered very good for the propagation and growth of various bananas in vitro at certain opti-mum concentrations, but the application of BA for the propagation is different for each type of banana because it depends on the need for different types and concentrations for each variety. Shirani et al (2009) found that the shoot proliferation rate was greatly affected by the type and concentration of cytokinins and the type of banana cultivar [19]. The addition of 7 ppm BA in MS media made a good contribution to the number of mulu bebe banana leaves related to the function of BA itself in encouraging cell division and the process of organogenesis in micropropagation.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…Cytokinins are always used with auxin to promote cell division, shoot proliferation, and differentiation of adventitious shoots. In addition, the cytokinins can mediate lateral bud release from apical dominance (Shirani et al 2009;Le Bris 2017;Pai and Desai 2018). Thidiazuron (TDZ) is a phenyl urea substitute that acts as a plant growth regulator to induce the regeneration of recalcitrant species in plant tissue culture (Erland et al 2020;Dinani et al 2021).…”
Section: Initiation and Multiplication Of In Vitro Shoots And Nodule-...mentioning
confidence: 99%